1988
DOI: 10.1017/s0022215100107546
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem auditory evoked potentials after irradiation of nasopharyngeal carcinoma—Report on two cases with myelopathy of the brainstem

Abstract: Brainstem auditory evoked potentials (BAEP) were recorded in two patients with nasopharyngeal carcinoma (NPC) irradiated 14 and three years ago respectively and compared with 15 healthy controls. The patients had features of post-irradiation myelopathy of the brainstem with reduced gag reflex, unilateral vocal cord paralysis and fasciculation of the tongue. The first patient had a blind left eye. The second patient had quadriparesis. All ears revealed post-irradiation otitis media changes and mixed deafness. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1992
1992
2003
2003

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…2c). In contrast to other studies, we could not detect other radiation-associated clinically relevant cranial nerve neuropathy [15] or hypothalamic pituitary axis dysfunction, as evidenced by normal TSH, thyroxine and cortisol levels [14]. These differences are perhaps due to the field reduction at a dose of 40 Gy in our patient.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…2c). In contrast to other studies, we could not detect other radiation-associated clinically relevant cranial nerve neuropathy [15] or hypothalamic pituitary axis dysfunction, as evidenced by normal TSH, thyroxine and cortisol levels [14]. These differences are perhaps due to the field reduction at a dose of 40 Gy in our patient.…”
Section: Discussioncontrasting
confidence: 99%
“…Histological studies have revealed that radiation induces a mucosal edema that impairs eustachian tube patency and produces middle ear fluid collection [18]. SHNL is caused by cochlear and/or retrocochlear damage [15,22]. Radiation-induced labyrinthitis was found in the bone conduction scores of our patient (Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In a prospective study, Kingston et al (1986) found four children who developed abnormally large interaural difference of waves I-V IPLI after RT and chemotherapy for head and neck malignancy. Prolonged waves I-V IPLI were also recorded from two NPC patients who had radiationinduced brain stem myelopathy (Lau et al, 1988).…”
Section: Introductionmentioning
confidence: 99%